Adrenal cortical adenoma arising in an adreno-hepatic fusion: Case report and literature review of a potential diagnostic pitfall - Adam Stenman; Ivan Shabo; Jan Zedenius; C. Christofer Juhlin (Elsevier, 2022)
Adrenal incidentalomas are commonly detected via routine radiological procedures, and any sign of grossly invasive properties may alert the clinical team to suspect malignancy. Adreno-hepatic fusion (AHF) is a developmental disorder in which the parenchyma of the right adrenal gland is partly or wholly fused with the liver. The development of an adrenal cortical tumor in AHFs is a rare phenomenon that may mimic an invasive lesion. The index patient is a 74-year-old male with an incidental finding of a 25 mm lesion in segment VI of the liver. The lesion was deemed as fat-containing with magnetic resonance imaging (MRI) scans, and no signal was obtained on fluorodeoxyglucose-positron emission tomography (FDG-PET). A core needle biopsy was taken, and histology displayed adrenal cortical tumor lacking pleomorphism, mitoses and necrosis intermingled with hepatocytes. The favored diagnosis was adrenal cortical adenoma (ACA) arising in an AHF. Surgical resection was subsequently performed, thus verifying the diagnosis. A review of the current literature identified 10 cases with ACA development in AHF, predominantly detected as incidental masses in older female patients, and always positive for markers of adrenal differentiation when assessed. We conclude that radiological evidence of an adrenal tumor adherent to the liver capsule should not automatically imply adrenal cortical carcinoma, especially if the tumor is small and FDG-PET negative. Although exceedingly rare, adenoma formation in a pre-existing AHF should constitute a differential diagnosis in this specific clinical setting. Moreover, adrenal cortical immunohistochemical markers seem to correctly identify the tissue origin in these rare malformations.